Economic Imperialists Attack! What Sociologists Should Do? - Radaev, Vadim (Journal of Economic Sociology, 2010)
Economists attack! The movement of economic imperialism comprises the systematic attempts of economic theory expansion into the nearby fields of social science. And this expansion is an indirect evidence for the internal crisis of economic theory [Guriev 2008]. Exit to external borders and revision of own assumptions go together in much sense supporting each other. But we believe that economists will manage to solve these problems themselves. We are interested in a different question: how should sociologists treat this situation. Remain calm and do nothing or to fight with “usurpers”?